Institutional Spheres and Organizational Sociology: Considering the Ecological and Cultural Dynamics of the Macro Realm - Abrutyn Seth; Uscola Colter; Feldstein Kate (Journal of Organizational Sociology, 2025)
Institutions remain essential units of sociological analysis, and yet they persist as conceptually fuzzy nearly five decades after the emergence of new institutionalism. In the following essay, a historical, comparative, and evolutionarily-informed framework for differentiating institutions from the individuals, organizations, and clusters of organizations that inhabit them is presented. Drawing from a diverse array of sociology, this model offers two key contributions to the study of organizations: an institutional ecological model built up from actors, organizations, and constellations of organizations and a theory of institutional culture that rests on a rehabilitated conceptualization of generalized symbolic media and its role in standardization and exchange between organizations. Implications are discussed.